Gender bias and the intrahousehold distribution of resources: Evidence from African nuclear households in South Africa - (:unkn) unknown (My University, 2018)
This paper applies recent developments in collective model estimation to elicit the allocation of resources in African families in South Africa. We use the 2010/11 South African Income and Expenditure Survey as it contains exclusive goods, i.e., goods con
Keywords: African Research